ILCA 1992: annual report and programme highlights - International Livestock Centre for Africa (International Livestock Centre for Africa, 1993)
This annual report and programme highlights presents highlights of ILCA's work in 1992 under the seven programme themes in the medium-term plan for 1994-1998. The highlight for the theme mixed crop-livestock systems focuses on ILCA's work on nutrient cycling in mixed crop-livestock systems in the Sahelian region. Market-oriented smallholder dairying carries a report of results from ILCA's work at the Kenya coast, and outlines a framework for research on smallholder dairying that was developed during 1992. The highlight on the theme conservation of biodiversity presents the programme developed in 1992, and outlines preliminary results of initial work gathering information on West African taurine breeds of cattle. ILCA's research in Kenya highlighted under biological efficiency of livestock, is providing evidence of genetic resistance to endoparasites in the Red Maasai breed of sheep. Further, the results show that this trait is heritable and may be selected for. The work of the African Trypanotolerant Livestock Network continues to yield insights into the mechanisms of trypanotolerance. The highlight for livestock and resource management policy focuses on a study of the influence of policy on peri-urban dairying in Kenya and Ethiopia. The focus of the report on strengthening national research capacities focuses on the role of training, particularly individual training, in ILCA's research programme. All these highlights point to the increasing strength of ILCA's research, training and information programme.